Uma mulher à sombra do rei: madame de Maintenon e a educação/A woman in the shadow of the the king - Agueda Bernardete Bittencourt (Universidade Estadual de Campinas, 2007)
Estudo sobre as raízes do pensamento e das práticas educacionais hoje estabelecidas na escola e na família através da reflexão sobre uma personagem, Madame de Maintenon, e sua obra escrita e aplicada na organização da primeira escola laica feminina na França de Louis XIV. Study on the roots of the thinking and on the educational practices set at schools and in the family nowadays, through the analysis of a character, Madame de Maintenon, and her written work applied in the organization of the first secular women school in France of Louis XIV.